Vulnerability of catfish to fishing: an investigation based on the landings - Raje, Sadashiv Gopal; Vivekanandan, E (Indian Journal of Fisheries, 2011)
The estimated annual average catch and catch rate of catfish by trawlers at New Ferry Wharf, Mumbai decreased from 2,586 t and 2.2 kg/h during 1991-1994 to 1,548 t and 1.0 kg/h during 1995-2004. Tachysurus tenuispinis, T. serratus and T. thalassinus Â max , males were rarely found. The presence of immature and mature ova in the same ovaries indicated that they are fractional spawners. The number of ripe eggs in the oro-buccal cavity of gestating males was always less than the number of eggs recorded in the ovary of females. Due to gestation behaviour, the males are more vulnerable to fishing. appear to be susceptible to fishing. T. thalassinus grow slowly, attain large size, mature late, get recruited early to the fishery, and a large majority are exploited before attaining first maturity. The sex ratio of five species of catfish was biased toward male when young, but the number of males substantially decreased in larger group, and at lengths closer to L